Notes on batoid fishes of the Socotra Archipelago (north-western Indian Ocean), with four new records - Bogorodsky, Sergey V.; Zajonz, Uwe; Saeed, Fouad N.; Weigmann, Simon (Zootaxa, 2021)
The species composition of batoid fishes from coastal waters of the Socotra Archipelago is reviewed, with confirmed records of the wedgefish Rhynchobatus djiddensis (Forsskål, 1775) and four new records of sharkrays, wedgefishes, and guitarfishes based on collected specimens, including one species from Abd al-Kuri Island, Rhina ancylostoma Bloch & Schneider, 1801 (Rhinidae), and three species from the main island Socotra, Acroteriobatus salalah (Randall & Compagno, 1995) and Rhinobatos punctifer Compagno & Randall, 1987 (Rhinobatidae), and Rhynchobatus australiae Whitley, 1939 (Rhinidae). Among the new records for the Socotra Archipelago, R. australiae represents the first verified record for the Arabian region. In addition, records of four stingray species (Dasyatidae) are verified based on underwater observations accompanied with photographs. All recorded batoid fishes are commercial species caught in the local small-scale fishery. Information on the identification and distribution of each species is provided.